Morphology and Cell Compatibility of Regenerated Ornithoctonus Huwenna Spider Silk by Electrospinning (Journal of Fiber Bioengineering and Informatics, 2008)
Ornithoctonus huwenna spiders can be bred in mass production, and potential applicationsof the spider silk in medical materials should be paid attentions. Regenerated nano-scale spider silknonwovens were prepared by electrospinning from tanglesome Ornithoctonus huwenna spider silk. Themorphologies of the electrospun spider silk fibers were investigated, and the cell compatibilities wereexplored. The results showed that the electric field strength was an important factor for the diameter,degree of crystal and molecular conformation of electrospun Ornithoctonus huwenna spider silk. Withthe increase of electric field strength, fibers became fine and even, and the crystallinity and